A novel modulation method for half-bridge based modular multilevel converter under submodule failure with reduced switching frequency - Kim, Seok Min; Lee, Kyo Beum; Lee, June Seok (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2019)
This paper proposes a novel modulation method for half-bridge submodule (SM) based modular multilevel converter (MMC) under faulty SM condition. When a SM is failed, the proper healthy SM is selected and the faulty SM is replaced by the healthy SM in the proposed fault-tolerant method. By replacing the faulty SM, the MMC continues its operation as the normal mode. The SM selection is implemented by a novel modulation method and it reduces the switching frequency of all healthy SMs, which is the serious drawback of the conventional sorting algorithm. The neutral-shift method is applied in order to maintain the balanced three-phase line-to-line voltages during a fundamental period. Various simulation studies verify that this post-fault strategy guarantees the balanced three-phase line-to-line voltages and currents as well as balancing of SM capacitor voltages without the aid of extra SMs.
Keywords: Capacitor voltages; Dc distribution; Fault-tolerant method; Fundamental period; Modular multi-level converters; Neutral shift; Simulation studies; Sorting algorithm; DC distribution; Fault-tolerance; Modular multilevel converter (MMC); Neutral-shift; Reliability